ПЕРЕХІДНІ ПРОЦЕСИ У РАЗІ ЗМІНЕННЯ КОНФІГУРАЦІЇ КОЛА РОЗРЯДУ КОНДЕНСАТОРА НАПІВПРОВІДНИКОВОЇ ЕЛЕКТРОРОЗРЯДНОЇ УСТАНОВКИ З ЕЛЕКТРОІСКРОВИМ НАВАНТАЖЕННЯМ - Супруновська, Н.І.; Щерба, М.А.; Михайленко, В.В.; Перетятко, Ю.В. (Інститут електродинаміки НАН України, Київ, 2020)
The method of multi-parameter functions is used in order to simplify the analysis of transients during the discharge of a capacitor to the electro-spark load in semiconductor electric discharge installations at changing the discharge circuit configuration for control the duration of the pulse currents in the load. On the basis of the analysis of transients in the discharge circuit of a variable structure of such installations, exact analytical expressions for calculating electrical characteristics of the circuit are obtained. It is determined the appropriate values of the connection moment and value of the additional inductance, which must be connected during the discharge of the capacitor to reduce the duration of discharge currents and stabilize the technological process in the electro-spark load. References 11, figures 8, tables 2.